Implementation of a Morphological Filter for Removing Spikes from the Epileptic Brain Signals to Improve Identification Ripples - Al-Bakri, Amir F; Martinek, Radek; Pelc, Mariusz; Zygarlicki, Jarosław; Kawala-Sterniuk, Aleksandra (Sensors, 2022)
Epilepsy is a very common disease affecting at least 1% of the population, comprising a number of over 50 million people. As many patients suffer from the drug-resistant version, the number of potential treatment methods is very small. However, since not only the treatment of epilepsy, but also its proper diagnosis or observation of brain signals from recordings are important research areas, in this paper, we address this very problem by developing a reliable technique for removing spikes and sharp transients from the baseline of the brain signal using a morphological filter. This allows much more precise identification of the so-called epileptic zone, which can then be resected, which is one of the methods of epilepsy treatment. We used eight patients with 5 KHz data set and depended upon the Staba 2002 algorithm as a reference to detect the ripples. We found that the average sensitivity and false detection rate of our technique are significant, and they are ∼94% and ∼14%, respectively.
Keywords: algoritmy; Humans; Epilepsy; lidé; epilepsie; elektroencefalografie; Brain; Brain Mapping; mapování mozku; mozek; Electroencephalography; Algorithms